'This scene is itself living': Buildings as landscapes in transatlantic human geography, 1870–1970. (July 2021) - Ekman, Peter
What do houses do to the people who live with them? In what sense are houses themselves living things? If they live and act, how to conceive of the relationship between built and natural landscapes, and between environment and life more broadly? This article considers three moments at which human geographers have attempted to answer these questions without submitting to visions of environmental causation and constraint favoured by determinists, who dominated the discipline into the early 20th century. The article begins with the work of Carl Sauer, by 1925 the major American figure refuting environmental determinism at a theoretical level and recommending the study of housing as an articulate transcript of human action. It then looks back to the American writings of Friedrich Ratzel, one of several German scholars Sauer canonized, to illuminate a more vitalistic ontology of domestic architecture, and an urbanism, untapped by Sauer when filing his dissent. It then looks ahead to mid-century studies of vernacular architecture – by those of Sauer's students friendlier to urban life than he was, and by the critic and publisher J. B. Jackson – to assess how this inheritance informed critiques of industrial modernity in the post-war United States. The article observes certain continuities, despite manifest tensions, between 'old' and 'new' cultural geographies. It also routes a long-standing set of debates concerning the relationship of materiality to meaning – and of spatial to social form – through the case of human geography, a peculiar interstice in the broader constellation of disciplines.